Strategi Penentuan Harga dan Analisis Kelayakan Usaha (BEP) pada UMKM Parfum - Anin Ladila; Hadi Mubarak; Daud Tampibolon (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This Community Service Program (PKM) aimed to improve the knowledge and entrepreneurial skills of members of the Family Welfare Empowerment Organization (PKK) in determining selling prices and conducting business feasibility analysis for laundry perfume products. The program was conducted on May 3, 2026, at RW 025 Griya Asri 2 Blocks G and F, Sumberjaya Village, South Tambun District, Bekasi Regency, involving approximately 50 participants consisting of PKK members, community leaders, and local residents. The implementation methods included lectures, discussions, hands-on training in laundry perfume production, simulations of Cost of Goods Sold (COGS) calculations, selling price determination, and Break-Even Point (BEP) analysis. The results showed a significant improvement in participants’ understanding of production cost calculation, pricing strategies, profit estimation, and business feasibility assessment. Based on the business simulation, the total production cost for 10 liters of laundry perfume was Rp333,600, resulting in a Cost of Goods Sold (COGS) of Rp33,360 per liter. By setting the selling price at Rp45,000 per liter, participants were able to identify a potential profit margin and evaluate the feasibility of the business. Furthermore, the program enhanced participants’ motivation to develop home-based entrepreneurial activities as an alternative source of family income. Therefore, this community service activity successfully contributed to strengthening entrepreneurial capacity and promoting economic empowerment among community members.